Mr. Penumbra's 24-hour bookstore - Sloan, Robin, 1979- (New York : Picador/Farrar, Straus and Giroux, 2013)
After a layoff during the Great Recession sidelines his tech career, Clay Jannon takes a job at the titular bookstore in San Francisco, and soon realizes that the establishment is a facade for a strange secret.
Keywords: Bookstores -- Employees -- Fiction; Bookstores -- California -- San Francisco -- Fiction